The Internet and the Nigerian Woman: A Case of Female Undergraduates - Joseph Wilson; Aisha Kolo Lawan (KOME: An International Journal of Pure Communication Inquiry)
The Internet has drastically changed information and knowledge sharing processes globally. It is a widely accepted medium for transformation and empowerment. Individuals, groups, communities and nations, including women in their quest for a gender sensitive society have adopted the Internet as a viable tool. However, despite the countless benefits of this important tool of communication, research, entertainment, publishing, and business, there are challenges that affect Internet access and use among female students at the University of Maiduguri, Nigeria. This paper examines Internet access and use among female undergraduates at a Nigerian University. Selected female undergraduates completed questionnaires. The findings shows that the university computer centre (University Cyber Café) is the major Internet access point among the respondents. Research (information searches and learning) ranked first in the uses of the Internet among respondents, with financial constraints as the major challenge to access and use of the Internet. Respondents found women-related websites useful. They derive a certain gratification from these sites. However, most respondents do not post or contribute material or information on the web. Their interaction with the web involves mostly downloading. The study concludes that Internet access and use status among female students at the University of Maiduguri and women in general would be greatly enhanced if women organizations concentrated on addressing the challenges identified in this study. Attention should be paid to this category of women (university students) who have the educational capabilities and Internet potential to impact women empowerment efforts.